Real Time Face-Tracking And Iris Localization - Razalli, Husniza (2009)
Robust, non-intrusive human eye detection problem has been a fundamental and challenging problem for computer vision area. Not only it is a problem of its own, it can be used to ease the problem of finding the locations of other facial features for recognition tasks and human-computer interaction purposes as well. Many previous works have the capability of determining the locations of the human eyes but the main task in this thesis is not only a vision system with eye detection capability. Our aim is to design a real-time, robust, scale-invariant face tracker system with human eye movement indication property using the movements of iris based on localization technique indicate from image processing and circle fitting technique. As a result, our eye tracker system was successfully implemented using non-intrusive webcam with less error.